EFL Pre-Service Teachers’ Perception of Their Readiness in Teaching Online during Covid-19 Pandemic - Sarini Dewi, Ni Komang (The Art of Teaching English as a Foreign Language (TATEFL), 2021)
As teacher candidate, students majoring in English Education is required to take a teaching practice in real classroom setting. However, due to Covid-19 pandemic, the scheme of teaching practice is changed to online setting. The current study investigated pre-service teachers’ perception of their readiness in teaching English online. This study was a qualitative study followed by five English teacher candidate. The data were collected using interview guide and were analyzed using thematic analysis. It was found that the pre-service teachers were already familiar with the use technology for teaching such as google classroom, Schoology, and Zoom. They mentioned that in terms of pedagogy, they are still uncertain about their readiness because of their lack experience. The study highlighted that the role of supervision in really importance in enhancing pre-service teachers’ competencies.